TLR2/4 are novel activating receptors for SARS-CoV-2 spike protein on NK cells - Landolina, Nadine; Ricci, Biancamaria; Veneziani, Irene; Alicata, Claudia; Mariotti, Francesca Romana; Pelosi, Andrea; Quatrini, Linda; Mortari, Eva Piano; Carsetti, Rita; Vacca, Paola; Tumino, Nicola; Azzarone, Bruno; et al. (Frontiers in Immunology, 2024)
Background: In early infected- or severe Coronavirus disease 2019 (COVID-19) patients circulating NK cells are consistently reduced, even though highly activated or exhausted. To establish whether Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) spike glycoprotein (SP) may directly trigger NK cells and through which receptor(s) is the aim of this paper. Methods: SP-stimulated human NK cells have been evaluated for the expression of activation markers, cytokine release, cytotoxic activity, as well as for gene expression profiles, NF-kB phosphorylation and silenced with specific small interfering RNAs. Results: SPs from the Wuhan strain and other Variants of Concern (VOC) directly bind and stimulate purified NK cells by increasing activation marker expression, cytokine release, and cytolytic activity, prevalently in the CD56brightNK cell subset. VOC-SPs differ in their ability to activate NK cells, G614 and Delta-Plus strains providing the strongest activity in the majority of donors. While VOC-SPs do not trigger ACE2, which is not expressed on NK cells, or other activating receptors, they directly and variably bind to both Toll-like receptor (TLR)2 and TLR4. Moreover, SP-driven NK cell functions are inhibited upon masking such receptors or silencing the relative genes. Lastly, VOC-SPs upregulate CD56dimNK cell functions in Covid-19 recovered, but not in non-infected, individuals. Conclusions: TLR2 and TLR4 are novel activating receptors for SP in NK cells, suggesting a new role of these cells in orchestrating the pathophysiology of SARS-CoV2 infection. The pathogenic relevance of this finding is highlighted by the fact that free SP providing NK cell activation, is frequently detected in SARS-CoV2 inflamed environment and in plasma of infected- and long-COVID‐19 subjects.